Avaliação de procedimentos de extração e determinação de boro em amostras de solo e plantas - Chaves, Fernanda Santiago (2006)
Boron is present in soils as an essential nutrient for plants growing. Soils and plants sample preparation procedures were evaluated aiming to compare the extractors efficiency. Sample preparation methods, such as dry and microwave digestions, extractions using heated water and pressurized water system, and chloride and acid solution extractions, were compared. The spectrophotometric and inductively coupled plasma optical emission spectrometry - ICP OES determinations were used to evaluated the method efficiency s of extraction and of decomposition. Sample preparation procedures for plants showed good results once recovery were approximately 100% when were compared with certificate values for SRM NIST (1515). Extraction method in soil employing water and barium chloride solution as extractors showed the best results. The methods using microwave-assisted presented the best agreements between themselves. The results obtained in analysis from Mehlich 1 and HCl 0,05 mol l-1 solution extractions were relatively lower then the others.